2017
DOI: 10.1111/jmi.12583
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sleep restriction disrupts interendothelial junctions in the hippocampus and increases blood–brain barrier permeability

Abstract: Chronic sleep loss in the rat increases blood-brain barrier permeability to Evans blue and FITC-dextrans in almost the whole brain and sleep recovery during short periods restores normal blood-brain barrier permeability. Sleep loss increases vesicle density in hippocampal endothelial cells and decreases tight junction protein expression. However, at the ultrastructural level the effect of chronic sleep loss on interendothelial junctions is unknown. In this study we characterised the ultrastructure of interendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
6
17
0
1
Order By: Relevance
“…Chronic sleep deprivation affects multiple physiological processes such as glucose metabolism, neuronal function, and cerebral blood flow that can ultimately contribute to diseases such as diabetes and Alzheimer's disease [130][131][132]. Chronic sleep disturbances in rodents result in decreased expression of TJ and increased paracellular permeability [132,133], indicating that disruption of the BBB might be a mechanistic component in pathologies associated with sleep deprivation. Moreover, in rats, disruption of rapid eye movement sleep has been shown to trigger BBB breakdown and increase transcytosis in brain ECs [134].…”
Section: Box 1 Bbb Tightness Is Modulated During Sleepmentioning
confidence: 99%
“…Chronic sleep deprivation affects multiple physiological processes such as glucose metabolism, neuronal function, and cerebral blood flow that can ultimately contribute to diseases such as diabetes and Alzheimer's disease [130][131][132]. Chronic sleep disturbances in rodents result in decreased expression of TJ and increased paracellular permeability [132,133], indicating that disruption of the BBB might be a mechanistic component in pathologies associated with sleep deprivation. Moreover, in rats, disruption of rapid eye movement sleep has been shown to trigger BBB breakdown and increase transcytosis in brain ECs [134].…”
Section: Box 1 Bbb Tightness Is Modulated During Sleepmentioning
confidence: 99%
“…Sleep restriction was performed using the multiple‐platform technique; briefly, males were placed in a transparent acrylic tank with five–seven platforms (7 cm diameter) surrounded by water. Animals were placed in the sleep‐restriction chamber for 20 hr per day for 10 consecutive days in groups of four–six; each day animals had sleep opportunity at their home‐cages for the last 4 hr of the light phase, as previously reported (Gómez‐González et al., ; Hurtado‐Alvarado et al., , ). An extra platform was added to the deprivation chamber in order to allow mobility and avoid restraint stress in the animals simultaneously deprived.…”
Section: Methodsmentioning
confidence: 99%
“…The consequences of sleep loss have been extensively studied in different physiological processes (for review, see Brown, ). We have shown that sleep restriction increases blood–brain barrier permeability to exogenous circulating tracers such as Na‐fluorescein, Evans blue and FITC‐dextrans (both 10‐ and 70‐kDa; Gómez‐González et al., ; Hurtado‐Alvarado, Domínguez‐Salazar, Velázquez‐Moctezuma, & Gómez‐González, ; Hurtado‐Alvarado et al., ), and the mechanism involves the disruption of inter‐endothelial tight junctions with concomitant disarrangement of the actin cytoskeleton (Hurtado‐Alvarado, Velázquez‐Moctezuma, & Gómez‐González, ). The blood–brain barrier and the blood–tissue barriers at the male reproductive tract share common barrier features; for example, both biological barriers express the tight junction proteins occludin and ZO‐1, as well as members of the claudin family (Mital, Hinton, & Dufour, ; Stanton, ), and both of them also express similar carrier systems (such as P‐glycoprotein, a member of the ATP‐binding cassette superfamily; Mruk, Su, & Cheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the hippocampal BBB permeability of sleeprestricted rats remains higher after 2 h of sleep recovery, unlike other brain areas such as the cortex and basal nuclei that have a complete restoration of basal BBB in this period (Gómez-González et al, 2013;Hurtado-Alvarado et al, 2017). However, 24 h of sleep recovery after sleep restriction is enough to restore the normal permeability of the BBB (He et al, 2014).…”
Section: The Role Of the Blood-brain Barrier In Cognitive Impairment Associated With Sleep Restrictionmentioning
confidence: 97%